2016
DOI: 10.1089/jmf.2015.3556
|View full text |Cite
|
Sign up to set email alerts
|

Cichorium intybus Linn. Extract Prevents Type 2 Diabetes Through Inhibition of NLRP3 Inflammasome Activation

Abstract: This study provides the scientific basis for the inhibitory effect of the aerial parts of Cichorium intybus Linn. (C. intybus) on the activation of the NLRP3 inflammasome in vitro and on high-fat diet (HFD)-induced type-2 diabetes (T2D). Lipopolysaccharide (LPS)-primed bone marrow-derived macrophages were used to study the effects methanolic extract of C. intybus leaf (CI) on inflammasome activation. An insulin resistance model (mice fed a HFD) was used to study the in vivo effect of CI on T2D. CI attenuated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…Therefore, many efforts have been made to find inhibitors that can control NLRP3 inflammasome activation from various sources such as small molecules, interferon, autophagy inducers, and microRNA [ 18 , 33 35 ]. In recent years, much attentions have been given to drug discovery from natural sources and their active constituents that can act as specific NLRP3 inflammasome inhibitor and many have been reported from others and our laboratory [ 36 38 ]. In our continuous search of specific inhibitors of NLRP3 inflammasome, we identified that the extracts of A. lappa leaves and stems suppressed the release of IL-1 β through NLRP3 inflammasome activation induced by typical agonists, such as ATP, nigericin, and silica crystals.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, many efforts have been made to find inhibitors that can control NLRP3 inflammasome activation from various sources such as small molecules, interferon, autophagy inducers, and microRNA [ 18 , 33 35 ]. In recent years, much attentions have been given to drug discovery from natural sources and their active constituents that can act as specific NLRP3 inflammasome inhibitor and many have been reported from others and our laboratory [ 36 38 ]. In our continuous search of specific inhibitors of NLRP3 inflammasome, we identified that the extracts of A. lappa leaves and stems suppressed the release of IL-1 β through NLRP3 inflammasome activation induced by typical agonists, such as ATP, nigericin, and silica crystals.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, exploring novel agents that have regulatory activity on the NLRP3 inflammasome might be an ideal therapeutic strategy for the treatment of inflammasome-mediated inflammatory diseases. Enormous efforts have been made in drug discovery, and in particular, traditional medicines have been important resources for treating inflammatory disorders [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is known that inflammasome activation is triggered by the self-oligomerization of NLRP3 26 , 27 , which in turn promotes ASC oligomerization to form the insoluble specks. In addition, NLRP3 as well as ASC translocate into insoluble fractions to form oligomers 7 , 28 30 , which can also be detected in the insoluble pellets of the Triton X-100-treated cell lysates 24 , 28 , 31 . Therefore, we examined the effects of BOT-4-one on the distribution of NLRP3 and ASC into the soluble and insoluble fractions.…”
Section: Resultsmentioning
confidence: 99%
“…NLRP3 alkylation is generally expected to reduce its ATP-binding affinity 9 , thereby resulting in impaired ATPase activity 10 , 11 . It has been previously shown that an NLRP3 mutant with impaired ATPase activity failed in self-oligomerization and the subsequent translocation into the detergent-insoluble fraction 7 , which are important processes of inflammasome activation 26 28 , 31 . The ATPase activity of NLRP3 is also important for its oligomeric association with ASC 7 , 8 , 10 .…”
Section: Discussionmentioning
confidence: 99%